2015
DOI: 10.1007/s13197-015-1966-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virgin coconut meal (VCM) on the rheological, micro-structure and baking properties of cake and batter

Abstract: Virgin coconut meal (VCM) cakes were prepared by replacing refined wheat flour (maida) (5 to 20 % level) to check its effect on chemical, textural and rheological attributes of cake. The addition of VCM significantly (p ≤ 0.05) increased redness (a*), yellowness (b*) while reduced lightness (L*) of cakes. The incorporation of VCM affects the hardness, adhesiveness gumminess and chewiness of cake. The effect of flour replacement with VCM increased the viscosity of batter which leads to increase in consistency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
3
1
0
1
Order By: Relevance
“…The cohesiveness and gumminess of the rice noodles significantly ( P < 0.05) decreased with the incorporation of DCF. The results of this study were similar to those reported by Srivastava & Semwal (2015), who found that adding virgin coconut meal to cake reduced its cohesiveness and gumminess value.…”
Section: Resultssupporting
confidence: 91%
“…The cohesiveness and gumminess of the rice noodles significantly ( P < 0.05) decreased with the incorporation of DCF. The results of this study were similar to those reported by Srivastava & Semwal (2015), who found that adding virgin coconut meal to cake reduced its cohesiveness and gumminess value.…”
Section: Resultssupporting
confidence: 91%
“…The values of this parameter increased significantly with the amount of FCM and FCO additions. Similar relationships were reported by Srivastava and Semwal, 37 who supplemented cake batter with different levels of coconut residue from oil production. No significant influence of the type of coconut raw material on the hardness of the rolls was noted.…”
Section: Resultssupporting
confidence: 84%
“…TEAC values increased with increasing of fortification level of cumin (CuS6 and CuC6) and caraway (CarS6 and CarC6) flour about 2 times in comparison with control bread (Figure 4). Higher TEAC values means greater antioxidant activity, nonetheless, our results are in accordance with previous studies that reported the positive effect of bread fortification on its antioxidant properties [18], [26].…”
Section: Trolox Equivalent Antioxidant Capacity (Teac) Analysissupporting
confidence: 93%